Catch Your Breath!: Vital Sensing for Radar - Wenzel, Marvin; Albrecht, Nils; Langer, Dominik; Heyder, Markus; Kölpin, Alexander (IEEE Microwave Magazine, 2023)
Vital signs are most essential in medical care to evaluate a patient's health situation. Today, electronic devices reliably measure the most important vital signs: heartbeat and respiration. Electrocardiography (ECG) measures the electrophysiological heart activity, while breathing can be detected with impedance pneumography (IP), which evaluates the periodic change of thorax impedance as we breathe in and out. While continuous monitoring of vital signs provides valuable medical information that can improve diagnostics, enable adaptive therapy, and generate new medical knowledge, there are also disadvantages. Medical procedures like ECG or IP require cables and electrodes, thus considerably reducing a patient's mobility. Furthermore, electrodes cause skin irritation if applied too long, which often limits the continuous monitoring of vital signs to situations of absolute medical necessity.
Created from Fastlane, Scopus look-up